BIBLIOMETRIC ANALYSIS OF INQUIRY-BASED LEARNING MODELS IN BIOLOGY ONLINE EDUCATION FOR ENHANCING HIGHER-ORDER THINKING SKILLS (HOTS) FROM 2013 TO 2023 - Lismaya, Lilis; Widyatmoko, Arif; Nurcahyono, Adi (Indonesian Journal of Learning and Instruction, 2024)
The rapid development of educational technology and increasing emphasis on Higher-Order Thinking Skills (HOTS) have made inquiry-based learning models in biology online education a crucial area of research. This study aims to analyze inquiry-based learning models in biology online learning using bibliometric analysis, focusing on publications from 2013 to 2023 sourced from the Google Scholar database. Out of an initial 298 articles, 53 relevant articles were identified and analyzed. The research methodology involved systematic stages, including keyword searches, refinement of results, data compilation, and analysis using tools like Microsoft Excel and VOSviewer software. The findings reveal that the number of publications on inquiry models in biology online learning fluctuates annually. Articles were categorized based on criteria such as the type of inquiry model (e.g., guided inquiry, free inquiry), variables studied, research locations, citation counts, HOTS components (e.g., critical thinking, problem-solving), types of online learning (e.g., interactive content, blended learning), and bibliometric visualizations. Notably, the study identified critical thinking and problem-solving as dominant HOTS aspects, while interactive content emerged as the most frequently used online learning type. The bibliometric visualization generated 14 thematic clusters, providing insights into research trends and gaps. This study offers valuable insights for researchers, educators, and policymakers interested in biology online learning. It highlights the potential for further exploration of underrepresented areas, such as decision-making and empirical research. The findings also serve as a guide for future studies to enhance the effectiveness of inquiry-based learning in fostering HOTS.Keywords: bibliometrics; biology; higher-order thinking skills; online learning.